Levels of matrix metalloproteinase-2 and metalloproteinase-9 in the cerebrospinal fluid of dogs with visceral leishmaniasis - Marangoni, N. R. [UNESP]; Melo, G. D. [UNESP]; Moraes, O. C. [UNESP]; Souza, M. S. [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; Machado, Gisele Fabrino [UNESP] (Wiley-Blackwell, 2011)
P>Inflammation causes increases in the level of matrix metalloproteinases (MMPs), which, in central nervous system (CNS), are associated with neuroinflammation and disruption of blood-brain barrier. Analysis of cerebrospinal fluid (CSF) is pivotal for detecting diseases in CNS and, although a specific diagnosis may not be achieved, this analysis is helpful to confirm the diagnosis or to rule out relevant differential diagnoses. This study examined the levels of MMP-2 and MMP-9 in the CSF of dogs using gelatin zymography to verify possible alterations in these enzymes during natural systemic infection with Leishmania chagasi. Latent and active forms of MMP-2 were detected in some dogs of both groups, with high levels in the control group. In contrast, latent and active forms of MMP-9 were detected only in some animals with leishmaniasis. These results clearly demonstrate that MMP-9 is elevated in CSF of dogs with visceral leishmaniasis (VL). Although these results are preliminary, they suggest that MMP-9 might play a role in disruption of blood-brain barrier and/or blood-CSF barrier. While the presence of MMPs in CSF is not a condition exclusive to VL, their presence and persistence in CSF supports the hypothesis of an inflammatory state within CNS of dogs with VL.
Keywords: central nervous system; inflammation; Leishmania chagasi; MMP-2; MMP-9; zymography